Understanding West German economic growth in the 1950s - Barry Eichengreen; Albrecht Ritschl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
We evaluate explanations for why Germany grew so quickly in the 1950s. The recent literature has emphasized convergence, structural change and institutional shake-up while minimizing the importance of the postwar shock. We show that this shock and its consequences were more important than neoclassical convergence and structural change in explaining the rapid growth of the West German economy in the 1950s. We find little support for the hypothesis of institutional shakeup. This suggests a different interpretation of post-World War II German economic growth than features in much of the literature.
Keywords: N14; N44; O52; 330; Economic growth; productivity; Germany; Wirtschaftswachstum; Produktivität; Kriegsschaden; Schock; Wirtschaftsgeschichte; Alte Bundesländer; Deutschland